Identification of Social Disasters as Non-Military Threats in Correctional Institutions and State Prisons in Indonesia - Bachri, Syamsul; Widodo, Pujo; Syahtaria, Moh. Ikhwan; ., Kusuma; ., Wilopo (Polteknik Ilmu Pemasyarakatan, 2024)
In the context of national security, social disasters are part of non-military threats because they are multidimensional because all events or series of events are caused by humans which include social conflict between groups or communities and terror. The aim of this research is to analyze the overcrowding problem that occurs in prisons and detention centers which has the potential to become a non-military threat based on disaster aspects and indicators of non-military defense threats. This research method uses a descriptive qualitative approach to analyze phenomena that are currently occurring. The research results show that there are five impacts caused by overcrowding as a social disaster which is a non-military threat, namely: 1 Social Conflict, 2 Prisonization of Crime Teaching, 3 Sexual Harassment, 4 Narcotics Smuggling, and 5 Discrimination. This is based on daily occupancy data held by the Directorate General of Corrections and through direct observations and secondary data obtained by researchers. Narcotics cases account for the largest number of residents in almost every prison and detention center in Indonesia. The research conclusion is that the development of the threat of social disaster caused by overcrowded conditions in prisons and detention centers has the potential to become a threat to non-military defense if seen from the disaster aspect and threat indicators.